2019
DOI: 10.3390/brainsci9120383
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Injury and Brain Growth in the Setting of Long-Gap Esophageal Atresia Perioperative Critical Care: A Pilot Study

Abstract: We previously showed that infants born with long-gap esophageal atresia (LGEA) demonstrate clinically significant brain MRI findings following repair with the Foker process. The current pilot study sought to identify any pre-existing (PRE-Foker process) signs of brain injury and to characterize brain and corpus callosum (CC) growth. Preterm and full-term infants (n = 3/group) underwent non-sedated brain MRI twice: before (PRE-Foker scan) and after (POST-Foker scan) completion of perioperative care. A neuroradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 81 publications
(128 reference statements)
3
17
1
Order By: Relevance
“…However, since no pre-treatment MRI scans were available, we could not rule out the possibility of inherently altered CC structure. Our preliminary findings implicate possible pre-existing (pre-Foker) CC findings 53 , similar to those previously reported for infants undergoing cardiac surgery and congenital diaphragmatic hernia 41 . (2) Study Groups: We lack a true control group since (1) there is no alternate treatment for LGEA that does not involve surgery, (2) there are a limited number of infants with prolonged sedation (without surgery) 11 , or (3) otherwise healthy preterm infants that did not require medical care.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, since no pre-treatment MRI scans were available, we could not rule out the possibility of inherently altered CC structure. Our preliminary findings implicate possible pre-existing (pre-Foker) CC findings 53 , similar to those previously reported for infants undergoing cardiac surgery and congenital diaphragmatic hernia 41 . (2) Study Groups: We lack a true control group since (1) there is no alternate treatment for LGEA that does not involve surgery, (2) there are a limited number of infants with prolonged sedation (without surgery) 11 , or (3) otherwise healthy preterm infants that did not require medical care.…”
Section: Discussionsupporting
confidence: 90%
“…Whether disparities in 3-D CC measures between patients and controls reflect pre-existing (prenatal) and/or delayed (postnatal; peri-surgery) CC maturation remains unclear and awaits future studies that should evaluate growth in contrast to size as described in this study. Our most recent preliminary data published as a small case report series 53 are in support of possible double-hit etiology of brain injury (pre-Foker and peri-Foker process) in both premature and full-term infants with LGEA. Both the degree of prematurity 54 and extremely low birth weight 55 have predicted smaller absolute CC volumes at term-equivalent age.…”
Section: Discussionsupporting
confidence: 66%
“…rophy in both full-term and pre-term patients [42] . On the other hand a recent study by Rudisill and coworkers demonstrated brain injury both before and after reconstructive surgery in EA patients and point out the need for knowledge about the pre-anesthesia intrinsic brain status to understand the mechanisms and the time of onset of the possible brain injury in EA patients [43] . Thus, even though the mechanisms of possible brain injury still need to be explored, recent research may seem to identify morphological substrates to the symptoms of trauma and mental impairment we register with the psychometric methods.…”
Section: Tablementioning
confidence: 99%
“…Furthermore, one may speculate if the patients are just growing into deficits in motor performance because of critical neonatal illness. Recently Rudisill et al suggested that delayed brain growth occurred during the perioperative period of repair of long gap EA [21] . Schiller et al proposed a common neurodevelopmental pathway to neuropsychological impairment following neonatal critical illness [22] .…”
Section: Discussionmentioning
confidence: 99%